Aggregation Behavior of Ionic Liquids in Aqueous Solutions: Effect of Alkyl Chain Length, Cations, and Anions - Singh, Tejwant; Kumar, Arvind (The journal of physical chemistry. B, 2007)
Self aggregation of the ionic liquids, 1-butyl-3-methylimidazolium chloride [C4mim][Cl], 3-methyl-1-octylimidazolium chloride [C8mim][Cl], 1-butyl-3-methylimidazolium tetrafluoroborate [C4mim][BF4], N-butyl-3-methylpyridinium chloride [C4mpy][Cl], in aqueous solution has been investigated through 1H nuclear magnetic resonance (NMR) and steady-state fluorescence spectroscopy. Aggregation properties were determined by application of mass action theory to the concentration dependence of 1H NMR chemical shifts. Aggregation properties showed fairly good agreement with the previously reported results obtained from small angle neutron scattering, conductivity, and surface tension measurements. A detailed analysis of chemical shifts of water and various protons in ILs has been employed to probe the aggregate structure. Fluorescence spectroscopy provided important information about the critical aggregation concentration (cac) and the microenvironment of the aggregates. We could also observe a break point quite consistent with that of 1H NMR and fluorescence spectroscopy at cac from the concentration dependence of refractive index measurements. Standard free energies of aggregation Δ of various ILs derived using the refractive index/concentration profiles were found comparable to those of classical ionic surfactants.